Isolation and Chracterization of Lactic Acid Bacteria from Bandeng (Chanos chanos) Bekasam - Joddi Iryadi Candra; Winarti Zahiruddin; . Desniar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2007)
Bekasam is one of the fishery product fermentation by using lactic acid bacteria. Bekasam is still made traditionally by applying spontaneous fermentation that cause product’s quality inconsistent. This research aims to analyze bacteria characteristics that isolated from bekasam and predict its types based on morphology and physiology characteristics. This research consists of three steps which are material analysis, isolation, and bacteria characterization. The result of this characterization is used to predict the bacteria type based on identification key. In this research milkfish bekasam is from traditional fishery product (pengolah) in Indramayu. It is predicted that milkfish has been fermented for two (2) weeks so that bekasam can be obtained. The analysis results shows that milkfish bekasam has Na Cl concentration 3.26 %, pH 4.46 and lactic acid total 1.30 %. Bacteria isolation from bekasam is chosen 5 (five) colony which grows dominantly and have different morphology. Those colony are isolated several times by quadrant scratch methode by using MRSA media until the pure culture can be obtained. The isolate are characterized based on morphology and physiology characteristic. Based onthe characterization result, it is predicted that isolate B1, B3, and B5 are bacteria Staphylococcus sp., isolate B2 is Erysipelothrix or Lactobacillus, and isolate B4 is family of Streptococcacea which are Streptococcus sp. or Gemella.Key words : characterization, fermentation, isolation, lactic acid bacteria, milkfish(Chanos chanos) bekasam